2004
DOI: 10.1016/j.ajic.2003.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of biofilm in catheter-associated urinary tract infection☆

Abstract: The predominant form of life for the majority of microorganisms in any hydrated biologic system is a cooperative community termed a "biofilm." A biofilm on an indwelling urinary catheter consists of adherent microorganisms, their extracellular products, and host components deposited on the catheter. The biofilm mode of life conveys a survival advantage to the microorganisms associated with it and, thus, biofilm on urinary catheters results in persistent infections that are resistant to antimicrobial therapy. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
271
1
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(289 citation statements)
references
References 97 publications
4
271
1
13
Order By: Relevance
“…Additionally, the catheter also damages the bladder mucosa by triggering inflammatory response and mechanical erosion [30]. Once bacteria gain entry into the urinary tract, low level bacteriuria progresses within 24 to 48 h in the absence of an antimicrobial therapy [31] [32] [33].…”
Section: Pathogenesis Of Catheter-associated Biofilmmentioning
confidence: 99%
“…Additionally, the catheter also damages the bladder mucosa by triggering inflammatory response and mechanical erosion [30]. Once bacteria gain entry into the urinary tract, low level bacteriuria progresses within 24 to 48 h in the absence of an antimicrobial therapy [31] [32] [33].…”
Section: Pathogenesis Of Catheter-associated Biofilmmentioning
confidence: 99%
“…Surface colonization by biofilm-forming bacteria is initiated by cell contact and adhesion to the surface [11][12][13]. The subsequent biofilm growth can cause highly resistant bacterial infections on medical implants and catheters or impaired industrial equipment [14][15][16][17][18][19].…”
mentioning
confidence: 99%
“…It was also found that there was significant correlation (p=0.27) between patient on long term antibiotic and infection with MDR isolates. Catheter care and frequent change would increase the response to antibiotic therapy (Trautner and Darouiche, 2004).…”
Section: Resultsmentioning
confidence: 99%